2019
DOI: 10.1111/1462-2920.14768
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid bacteria encode two levansucrase types of different ecological relationship

Abstract: Summary Acetic acid bacteria (AAB) are associated with plants and insects. Determinants for the targeting and occupation of these widely different environments are unknown. However, most of these natural habitats share plant‐derived sucrose, which can be metabolized by some AAB via polyfructose building levansucrases (LS) known to be involved in biofilm formation. Here, we propose two LS types (T) encoded by AAB as determinants for habitat selection, which emerged from vertical (T1) and horizontal (T2) lines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…However, it is yet unknown to what extent the size of levan influences its rheological properties. It was previously shown that levans produced by G. albidus TMW 2.1191 without external pH control are comparatively smaller in size at prolonged fermentation times, which might be due to (a combination of) continuous acidic hydrolysis, the intrinsic β-fructosidase activities of levansucrases or possibly additionally expressed β-fructosidases [10,20,35,36]. Accordingly, in the present study, the levan recovered from NaG medium after 48 h of incubation exhibited the lowest hydrodynamic volume/radius, at which an elevated nitrogen content was determined for this levan in comparison to the levans produced in Na-acetate buffers (pH 4.0 and 5.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is yet unknown to what extent the size of levan influences its rheological properties. It was previously shown that levans produced by G. albidus TMW 2.1191 without external pH control are comparatively smaller in size at prolonged fermentation times, which might be due to (a combination of) continuous acidic hydrolysis, the intrinsic β-fructosidase activities of levansucrases or possibly additionally expressed β-fructosidases [10,20,35,36]. Accordingly, in the present study, the levan recovered from NaG medium after 48 h of incubation exhibited the lowest hydrodynamic volume/radius, at which an elevated nitrogen content was determined for this levan in comparison to the levans produced in Na-acetate buffers (pH 4.0 and 5.0).…”
Section: Discussionmentioning
confidence: 99%
“…or Gluconobacter spp. produce levans [4][5][6][7][8][9][10]. Hence, levan is a natural component of sucrose-containing fermented foods such as sourdough breads [11], kefir [12] or natto [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is yet unknown to which extent the size of levan in fact influences its rheological properties. It was previously shown that levans produced by G. albidus TMW 2.1191 without external pH control are comparatively smaller in size at prolonged fermentation times, which might be due to (a combination of) continuous acidic hydrolysis, the intrinsic β-fructosidase activities of levansucrases or possibly additionally expressed β-fructosidases [9,19,32,33]. Accordingly, the levan recovered from NaG medium after 48 h of incubation in the present study exhibited the lowest hydrodynamic volume/radius.…”
Section: Discussionmentioning
confidence: 47%
“…or Gluconobacter spp. produce levans [3][4][5][6][7][8][9]. Hence, levan is a natural component of sucrose containing fermented foods like sourdough breads [10], kefir [11] or natto [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…6 ? Supplementary File 2), an additional expressed b-fructosidase (WP077802344) (Brandt et al 2017;Jakob et al 2019) and/or the possible intrinsic levanase activity (Méndez-Lorenzo et al 2015) of the levansucrase at certain conditions. The presented experimental approach could hence be used to control and trigger the sizes of globular levan molecules.…”
Section: Discussionmentioning
confidence: 99%